Perkembangan Sosial Masyarakat Indonesia Sepanjang Sejarah - Meiridha Utari Siregar; Jamilatul Khoiriyah; Rika Nanda Hayani; Aisyah Amini (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
The term history comes from Arabic, namely from the word syajaratun (pronounced syajarah), which means a tree of wood. The meaning of a wooden tree here is the existence of an event, development or growth of something (event) in a continuity (continuity). In another sense, history is not always defined by past (history is past actuality). Only in a general sense is the reality of the past. As for the social (social) itself can be interpreted with regard to interpersonal behavior, or related to social processes. But seen in social science, the word social refers to its object, namely society. When combined between history and social, it can be interpreted as the past reality of a society regarding behavior and all the processes that occurred in society. Social history is history that focuses attention on neglected, alienated, or marginalized people who are actors of social history. The roles of the community in an event in the past are the focus of the discussion of social history. This study aims to examine the social development of Indonesian society throughout history. Use a qualitative approach and include information from secondary data sources, previous research or existing knowledge of organizations and institutions. The data collection method used by the author in this article, the author uses the library method (path search). The library method is a method used to collect information from books and magazines. Where this social history is populist. Thus it is very different from conventional political history which is elitist in nature. It can be said that without social history, the existence of economic history will feel bland and shallow because social history provides the necessary link in economic history where the scope can cover the daily life of the inhabitants of an area in the past, which includes humans with different economic relationships. -different.